Konsep Administrasi Kurikulum Dalam Pendidikan - Yogi Fernando; Nova Mariyanti; Darul Ilmi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The curriculum is very important in the educational process because it is the driving force that determines the direction of education. Designing, managing, and developing curriculum requires something called curriculum administration. The administration of this curriculum aims to support the learning process and achieve the expected goals. This article is written using literature research methods and documents with readings relevant to the research being discussed. Curriculum administration activities include curriculum planning, implementation, supervision and evaluation. Curriculum administration helps to improve the appropriateness of the use of resources to increase the relevance and effectiveness of the learning process